Experimental Validation of Antiobesogenic and Osteoprotective Efficacy of Ginsenoside CK via Targeting Lipid and Atherosclerosis Pathways - Md. Niaj Morshed; Reshmi Akter; Imran Mahmud; Ah-Yeong Gwon; Jin Woo Jeang; Yeong-Geun Lee; Dae Won Park; Deok Chun Yang; Yeon Ju Kim; Se-Chan Kang (Life)
The present study explored the possible antiobesogenic and osteoprotective properties of the gut metabolite ginsenoside CK to clarify its influence on lipid and atherosclerosis pathways, thereby validating previously published hypotheses. These hypotheses were validated by harvesting and cultivating 3T3-L1 and MC3T3-E1 in adipogenic and osteogenic media with varying concentrations of CK. We assessed the differentiation of adipocytes and osteoblasts in these cell lines by applying the most effective doses of CK that we initially selected. Using 3T3-L1 adipocytes in vitro assessments, CK could effectively decrease intracellular lipid accumulation, inhibit α-glucosidase enzyme, increase 2-NBDG glucose uptake, reduce inflammation-associated cytokines (TNFα, and IL-6), adipogenic regulatory genes (PPARγ, FAS, C/EBPα), lipogenic gene LPL, and increase the expression of thermogenic gene UCP1. Additionally, CK treatment induced osteoblast development in MC3T3-E1 cells as shown by increased mineralization and calcium distribution, collagen content, alkaline phosphatase activity, and decreased inflammatory cytokines TNFα, and IL-6 and increased the regulated expressions of osteogenic genes including Runx2, ALP, BGLAP, OCN, and Col1a1. Significantly, as a major inhibitory regulator, the TP53 gene was down-regulated in both 3T3-L1 and MC3T3E1 cells after the treatment of CK. These encouraging results demonstrate the possible use of CK as an innovative treatment for controlling obesity and osteoporosis, targeting the underlying mechanisms of obesogenic and bone loss. Further studies are necessary to explore the clinical implications of these results and the potential of CK in future treatment strategies. This research highlights the promise of CK in addressing significant health issues.